Molecular Epidemiology and Antifungal Susceptibility of Candida glabrata in China (August 2009 to July 2014): A Multi-Center Study - Hou, Xin; Xiao, Meng; Chen, Sharon C.-A.; Kong, Fanrong; Wang, He; Chu, Yun-Zhuo; Kang, Mei; Sun, Zi-Yong; Hu, Zhi-Dong; Li, Ruo-Yu; Lu, Juan; Liao, Kang; et al. (Frontiers in Microbiology, 2017)
Candida glabrata is an increasingly importance cause of invasive candidiasis. In China, relatively little is known of the molecular epidemiology of C. glabrata and of its antifungal susceptibility patterns. Here we studied 411 non-duplicate C. glabrata isolates from 411 patients at 11 hospitals participating in the National China Hospital Invasive Fungal Surveillance Net program (CHIF-NET; 2010-2014). Genotyping was performed using multilocus sequence typing (MLST) employing six genetic loci and by microsatellite analysis. Antifungal susceptibility testing was performed using Sensititre YeastOneTM YO10 methodology. Of 411 isolates, 35 sequence types (ST) were identified by MLST and 79 different genotypes by microsatellite typing; the latter had higher discriminatory power than MLST in the molecular typing of C. glabrata. Using MLST, ST7 and ST3 were the most common STs (66.4% and 9.5% of all isolates, respectively) with 24 novel STs identified; the most common microsatellite types were T25 (30.4% of all isolates) and T31 (12.4%). Resistance to fluconazole (MIC >32µg/mL) was seen in 16.5% (68/411) of isolates whilst MICs of >0.5µg/mL for voriconazole, >2µg/mL for itraconazole and >2µg/mL for posaconazole were seen for 28.7%, 6.8% and 7.3% of isolates, respectively; 14.8% of all isolates cross-resistant/non-wide-type to fluconazole and voriconazole. Fluconazole resistant rates increased 3-fold over the 5-year period whilst that of isolates with non-WT MICs to voriconazole, 7-fold. All echinocandins exhibited >99% susceptibility rates against all isolates but notably one isolate exhibited multi-drug resistance to the azoles and echinocandins. The study has provided a global picture of the molecular epidemiology and drug resistance rates of C. glabrata in China during the period of the study.